Marketing Communication Strategies in Increasing the Number of Visitors to Karaoke Night Bernyanyi Bermasa - Ian Bonita; Tuti Bahfiarti; Alem Febri Sonni (UM Purwokerto Press, 2023)
People's need for night entertainment is no longer a new thing, especially for the city of Makassar. Night entertainment has now become a necessity for the young to the old to be one of the entertainments in the midst of busy activities. As time goes by, nightlife venues are now being enlivened with karaoke nights. Singing various genres of music together guided by a lead that has its own charm for visitors. The background of this study aims to determine how the form of marketing communication strategy of Karaoke Night Bernyanyi Bermasa in increasing the number of visitors and what factors support the marketing communication strategy in increasing the number of visitors to karaoke Night Bernyanyi Bermasa. This research will use purposive sampling technique, this technique includes based on the object. Where the population that meets the criteria is not sampled. Informants in this study amounted to 5 people consisting of 1 founder of Masa Kreatif, 1 employee of Teratas Bar, and 3 visitors to Bernyanyi Bermasa. The marketing strategy carried out at Bernyanyi Bermasa karaoke night in increasing the number of visitors through advertising, sales promotion, personal selling, publicity, direct marketing. From the marketing communication strategy carried out by Bernyanyi Bermasa karaoke night, it has not been maximized. Bernyanyi Bermasa has employees with diverse backgrounds in terms of social environment and age, strategic location with complete facilities and facilities as supporting factors. The inhibiting factor of marketing communication strategy at karaoke night Bernyanyi Bermasa is the lack of advertising and promotion.